REPRESENTATION OF WOMEN’S ROLE IN SUMBANESE IKAT WEAVING (TENUN IKAT) - Krisnadi, Tasya Widya (UI Scholars Hub, 2025)
The craft of weaving is not merely an economic or artistic activity, but also plays a central role in the identity and social life of the Sumba community, particularly in the Kodi District of Southwest Sumba Regency. Women in Sumba play a crucial role in the practice of tenun ikat. They are not only the custodians of the skills and technical knowledge of weaving, but also the bearers of cultural values embedded in the process. This research aims to reveal the role of Sumbanese women as preservers of tradition amidst the currents of modernization. This study employs qualitative methods with a descriptive approach through data analysis from interviews, literature review, and documentation. This research explores three main aspects: (1) the meanings that Sumbanese women ascribe to their roles in preserving the tenun ikat tradition, (2) the use of tenun ikat as a medium of cultural identity expression, and (3) the impact of weaving practices on Sumba community’s social and economic dynamics. The findings indicate that Sumbanese women are not merely passive transmitters of tradition, but also active agents who transform and adapt tenun ikat practices to assert their identities and respond to socioeconomic changes. This study contributes to a more nuanced understanding of the intersections between gender, tradition, and social change within the context of Indigenous Indonesian communities, while also highlighting the potential of local knowledge as a source of women empowerment. The implications of this research are relevant for developing cultural preservation policies that are more inclusive and sustainable.